Bonded body and ceramic circuit board using same
By forming a titanium nitride layer containing 1 at % or more in the bonding layer between the nitride-based ceramic member and the metal member of the ceramic circuit substrate, the problem of insufficient oxygen in the prior art is solved, and the bonding is improved Strength and thermal cycle test characteristics.
Patent Information
- Application Number
- CN202480003137.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-17
- Filing Date
- 2024-01-26
- Publication Date
- 2025-02-21
AI Technical Summary
The amount of oxygen in the titanium nitride layer of the existing ceramic circuit substrate is insufficient, resulting in the failure to effectively improve the bonding strength and thermal cycle testing characteristics.
By forming a titanium nitride layer containing 1 at % or more of oxygen in the bonding layer between the nitride ceramic member and the metal member, the oxygen amount of the titanium nitride layer is within a predetermined range.
The physical uniformity and bonding strength of the titanium nitride layer are improved, and the thermal cycle testing characteristics of the ceramic circuit substrate are enhanced.
Smart Images

Figure CN119497706A_ABST
Abstract
Description
Technical Field
[0001] The embodiments described below generally relate to a bonded body and a ceramic circuit board using the same. Background Art
[0002] In recent years, ceramic circuit substrates with good heat dissipation and thermal cycle test (TCT) characteristics have been developed. For example, in Japanese Patent Gazette No. 6789955 (Patent Document 1), a ceramic circuit substrate in which a ceramic substrate and a copper plate are bonded via a bonding layer is disclosed. In Patent Document 1, silicon nitride substrates, aluminum nitride substrates, aluminum oxide substrates, etc. are disclosed. Silicon nitride substrates and aluminum nitride substrates are called nitride-based ceramic substrates. Silicon nitride substrates have a three-point bending strength of more than 500 MPa, which is high strength. In addition, aluminum nitride substrates have a thermal conductivity of more than 160 W / m·K, which is high thermal conductivity. Nitride-based ceramic substrates have excellent performance compared to oxide-based ceramic substrates.
[0003] In Patent Document 1, an active metal brazing filler metal is used to join a nitride-based ceramic substrate and a copper plate. The active metal brazing filler metal is a brazing filler metal containing titanium as an active metal. A joint body can be obtained by applying the active metal brazing filler metal between the nitride-based ceramic substrate and the copper plate and performing heat joining. By performing heat joining, the active metal brazing filler metal layer becomes a joining layer. The active metal brazing filler metal containing titanium reacts with the nitride-based ceramic substrate to form a titanium nitride layer. By forming a titanium nitride layer on the surface of the nitride-based ceramic substrate as a part of the joining layer, the joining strength can be improved.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 6789955
[0007] Patent Document 2: Japanese Patent No. 4077888
[0008] Patent Document 3: Japanese Patent Application Publication No. 2013-211546
[0009] Patent Document 4: International Publication No. 2021 / 015122
[0010] Patent Document 5: International Publication No. 2022 / 244769 Summary of the invention
[0011] Problems to be solved by the invention
[0012] In Patent Document 1, the bonding layer has an extension extending from the end of the copper plate. By controlling the size and hardness of the extension, the TCT characteristics are improved. However, no performance improvement above this is seen. The reason for this is investigated, and it is found that it is due to the amount of oxygen in the titanium nitride layer. The titanium nitride layer is a hard material. For example, in Japanese Patent Gazette No. 4077888 (Patent Document 2), the Vickers hardness HV of the titanium nitride layer is as high as 1100 or more. In Patent Document 2, the titanium nitride layer is hardened by containing Cu and Al in the titanium nitride layer, thereby improving the TCT characteristics. Cu is a component contained in the brazing material, and Al is a component contained in the aluminum nitride substrate. These components are difficult to disperse evenly. Due to the uneven dispersion state in the titanium nitride layer, the physical properties of the titanium nitride layer are partially uneven.
[0013] Conventionally, the content of oxygen in the titanium nitride layer is very small. For example, in Japanese Patent Application Publication No. 2013-211546 (Patent Document 3), Figure 2 In the figure, the results of linear analysis of the cross-sectional direction of the ceramic circuit substrate using EPMA (electron beam microanalyzer) are shown. Regarding the oxygen content, the relative intensity (%) in the titanium nitride layer is small. It should be noted that with regard to the results described in Patent Document 3, the background has a large influence and the exact amount of oxygen cannot be grasped. In addition, in Table 1 of International Publication No. 2021 / 015122 (Patent Document 4), the oxygen content in the titanium nitride layer (interface layer 121, nanoparticle layer 131) is 0at%.
[0014] The present invention improves such a problem and provides a bonded body in which a predetermined amount of oxygen is contained in a titanium nitride layer.
[0015] Means for solving problems
[0016] The joint body of the embodiment comprises a nitride-based ceramic component and a metal component joined to the nitride-based ceramic component via a joining layer. A titanium nitride layer having titanium nitride as a main component is formed at the interface between the nitride-based ceramic component and the joining layer. The titanium nitride layer includes a portion having an oxygen content of 1 at % or more. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a diagram showing an example of a joined body according to an embodiment.
[0018] Figure 2 This is a diagram showing an example of a measurement region of a titanium nitride layer.
[0019] Figure 3 It is a diagram showing an example of a ceramic circuit board according to an embodiment.
[0020] Figure 4 This is a side view showing an example of a semiconductor device according to an embodiment. DETAILED DESCRIPTION
[0021] The joint body of the embodiment comprises a nitride-based ceramic component and a metal component joined to the nitride-based ceramic component via a joining layer. A titanium nitride layer having titanium nitride as a main component is formed at the interface between the nitride-based ceramic component and the joining layer. The titanium nitride layer includes a portion having an oxygen content of 1 at % or more.
[0022] Figure 1 This is a side view showing an example of a joined body according to the embodiment. Figure 2 FIG. 1 is a cross-sectional view showing an example of a measurement area of a titanium nitride layer. Figure 1 and Figure 2 , symbol 1 is a joint body, symbol 2 is a nitride-based ceramic component, symbol 3 is a metal component, symbol 4 is a joint layer, symbol 5 is a titanium nitride layer, symbol 6 is a measurement area, symbol 7 is a brazing material layer, and symbol 9 is a Ti-rich area.
[0023] The metal member 3 is bonded to the nitride-based ceramic member 2 via the bonding layer 4 . Figure 1 The figure shows an example in which metal components 3 are bonded to both surfaces of a nitride-based ceramic component 2. The metal component 3 may be bonded to only one surface of the nitride-based ceramic component 2. The number of metal components 3 bonded to one surface of the nitride-based ceramic component 2 is not limited to one, and may be two or more.
[0024] Nitride-based ceramic components are ceramic sintered bodies containing nitrogen as a constituent element. Examples of nitride-based ceramic components include silicon nitride sintered bodies (including Sialon sintered bodies) and aluminum nitride sintered bodies. Sintering aids may be added as needed. Examples of sintering aids include one or more compounds selected from rare earth elements, magnesium, titanium, and hafnium. Compounds added as sintering aids include oxides, nitrides, oxynitrides, silicides, and the like. Examples of rare earth elements include yttrium and lanthanide elements.
[0025] The nitride-based ceramic component 2 is formed into a substrate shape when used for a ceramic circuit substrate described later. The nitride-based ceramic component in the shape of a substrate is referred to as a nitride-based ceramic substrate. The thickness of the nitride-based ceramic substrate is preferably within a range of 0.1 mm to 3 mm. If the thickness is less than 0.1 mm, the strength of the nitride-based ceramic substrate may be insufficient. If the thickness exceeds 3 mm, the heat dissipation of the nitride-based ceramic substrate may be adversely affected.
[0026] A substrate made of a silicon nitride sintered body is called a silicon nitride substrate. The three-point bending strength of the silicon nitride substrate is preferably 500 MPa or more, more preferably 600 MPa or more. By improving the strength, the desired durability can be obtained even if the thickness of the substrate is reduced to 0.1 mm or more and 4 mm or less. In addition, the thermal conductivity of the silicon nitride substrate is preferably 50 W / m·K or more, more preferably 80 W / m·K or more. By increasing the thermal conductivity, the heat dissipation can be improved. The fracture toughness value of the silicon nitride substrate is preferably 5.5 MPa·m 1 / 2 above.
[0027] A substrate made of an aluminum nitride sintered body is called an aluminum nitride substrate. The thermal conductivity of the aluminum nitride substrate is preferably 160 W / m·K or more. The three-point bending strength of the aluminum nitride substrate is preferably 300 MPa or more. Although the aluminum nitride substrate has a higher thermal conductivity than the silicon nitride substrate, the mainstream is an aluminum nitride substrate with a strength of less than 500 MPa. Therefore, the aluminum nitride substrate is not suitable for thinning the substrate. From the viewpoint of thinning the substrate, a silicon nitride substrate is preferred.
[0028] The three-point bending strength is measured by the measurement method based on JIS-R-1601 (2008). The thermal conductivity is measured using the flash method. The fracture toughness value is calculated using the new formula using the measurement method based on the IF method of JIS-R-1607 (2015). JIS-R-1601 corresponds to ISO14704. JIS-R-1607 corresponds to ISO15732.
[0029] The metal component 3 is an aluminum component or a copper component. The material of the aluminum component is aluminum, an aluminum alloy, etc. The material of the copper component is pure copper, a copper alloy, etc. As pure copper, oxygen-free copper can be listed. Oxygen-free copper is specified in JIS-H-3100. JIS-H-3100 corresponds to ISO1337, etc. Here, a copper component having a plate shape is referred to as a copper plate. When used for a ceramic circuit substrate, the thickness of the copper plate is preferably in the range of 0.1 mm or more and 5 mm or less.
[0030] In the bonded body 1, the nitride-based ceramic member 2 and the copper member are bonded via the bonding layer 4. At the interface between the nitride-based ceramic member 2 and the bonding layer 4, a titanium nitride layer 5 containing titanium nitride as a main component is formed.
[0031] The bonding layer 4 is formed by heating and bonding an active metal brazing filler metal. The active metal brazing filler metal contains titanium (Ti) as an active metal. In the heating and bonding process, the titanium in the active metal reacts with the nitrogen in the nitride-based ceramic component to form a titanium nitride layer 5. Therefore, a titanium nitride layer 5 is formed at the interface between the nitride-based ceramic component 2 and the bonding layer 4.
[0032] The titanium nitride layer 5 refers to a region where the total amount of titanium and nitrogen is greater than 70 at %. Preferably, the titanium nitride layer 5 is a region where the total amount of titanium and nitrogen is greater than 90 at % and less than 100 at %. In addition, the titanium nitride layer 5 refers to a region where the total amount of titanium and nitrogen is greater than 70 at % and less than 100 at % connected to the surface direction of the nitride-based ceramic component 2 for more than 5 μm.
[0033] As described below, the portion of the titanium nitride layer 5 where the oxygen content is measured is a region where the total amount of titanium and nitrogen is 70 at % or more and 100 at % or less. The titanium nitride layer 5 is preferably present in contact with the nitride-based ceramic member 2 .
[0034] The measurement of the oxygen content in the titanium nitride layer 5 was performed in two stages using regional analysis using TEM-EDX. The first regional analysis was performed to identify the titanium nitride layer 5 in the bonding layer 4. The second regional analysis was performed to measure the oxygen content in a micro region in the titanium nitride layer 5.
[0035] First, the measurement method using TEM-EDX is described. TEM is a transmission electron microscope (Transmission Electron Microscopy). EDX is an energy dispersive X-ray spectroscopy (Energy Dispersive X-ray Spectroscopy). EDX is sometimes also called EDS. Sometimes TEM-EDX analysis is also referred to as EDX analysis.
[0036] As a sample for EDX analysis, an arbitrary cross section of the joint body 1 is used. From an arbitrary cross section, the sample is collected by focused ion beam (FIB) processing or ion milling processing. The thickness of the sample is preferably within the range of 0.05 μm or more and 0.1 μm or less (50 nm or more and 100 nm or less). In order to prevent surface oxidation of the sample, the sample is preferably made in a vacuum or in an inert gas atmosphere and stored.
[0037] As an EDX device, a JED-2300T manufactured by JEOL or a device having equivalent or higher performance is used. As a TEM, a JEM-200CX manufactured by JEOL (accelerating voltage 200 kV) or a device having equivalent or higher performance is used. The recommended conditions for EDX analysis are an accelerating voltage of 200 kV and a spot diameter of 1 nm during analysis. The recommended analysis time is 10 seconds or more and 15 seconds or less, and the sample tilt angle is X=0°, Y=0°. As long as a measurement area of 20 nm×20 nm can be ensured, the direction of the sample is arbitrary.
[0038] TEM-EDX is suitable for analyzing micro areas. The measurement area 6 is selected from a portion that is more than 0.5 mm away from the edge surface of the bonding layer. The portion within 0.5 mm from the edge surface may be affected by external contamination during storage. The edge surface is the outer edge of the bonding layer of the bonded body and is the portion that is in direct contact with the outside air.
[0039] In the first regional analysis, the size of the measurement area in the surface direction of the nitride-based ceramic component 2 is set to be greater than 5 μm. Through the first regional analysis, the distribution of titanium and nitrogen in a wide range of the bonding layer 4 is observed. From the distribution of titanium and nitrogen, the area in which the total amount of titanium and nitrogen is greater than 70 at% and which is connected to the surface direction of the nitride-based ceramic component 2 for more than 5 μm is determined as the titanium nitride layer 5.
[0040] In the second regional analysis, a 20 nm × 20 nm region is selected from the region determined to be the titanium nitride layer 5 in the first regional analysis as the measurement region 6. As the measurement region, any five regions separated from each other are selected. The average value of the proportions of the elements obtained in the five regional analyses is calculated. The average value sets the total of the constituent elements other than carbon to 100 at%. Carbon is excluded to eliminate the influence of the situation where the titanium nitride layer 5 reacts with the atmosphere and is carbonized by electron beam irradiation during analysis. When the total of the constituent elements other than carbon is set to 100 at%, it is preferred that the average value of the oxygen content in any five measurement regions is 1 at% or more, and the average value of the nitrogen content in the five measurement regions is 20 at% or more.
[0041] In the first regional analysis, the content of titanium and nitrogen at each point in a wide range is measured. In the second regional analysis, the content of each element in the entire measurement area of 20nm×20nm is measured. The resolution is different in the first regional analysis and the second regional analysis. Therefore, even in the area determined as the titanium nitride layer 5 by the first regional analysis, the total content of titanium and nitrogen may be less than 70at% when the second regional analysis is performed. In this case, the measurement area where the total content of titanium and nitrogen is less than 70at% is not selected as the area for measuring the nitrogen amount or oxygen amount.
[0042] In the titanium nitride layer 5, the fewer the areas where the total amount of titanium and nitrogen is measured to be less than 70at% by the second regional analysis, the better. In the case where there are parts where the total amount of titanium and nitrogen is measured to be less than 70at% in the second regional analysis, the area ratio is preferably 10% or less, and more preferably 5% or less. The "area ratio" is expressed as the ratio of the number of areas where the total amount of titanium and nitrogen is measured to be less than 70at% relative to the number of 20nm×20nm measurement areas where the second regional analysis is performed. For example, when the second regional analysis is performed on 20 measurement areas, in which the total amount of titanium and nitrogen is less than 70at% in one measurement area, the area ratio becomes 5%.
[0043] It should be noted that the above-mentioned constituent elements other than carbon are all elements other than carbon detected by TEM-EDX. The constituent elements are components of the nitride-based ceramic member, components of the active metal brazing filler metal, oxygen, and nitrogen.
[0044] For example, when the nitride-based ceramic component is a silicon nitride sintered body, the constituent elements are Si (silicon), N (nitrogen) and a sintering aid. When the nitride-based ceramic component is an aluminum nitride sintered body, the constituent elements are Al (aluminum), N (nitrogen) and a sintering aid. When yttrium oxide and magnesium oxide are used in the sintering aid, the constituent elements derived from the sintering aid are Y (yttrium), Mg (magnesium), and O (oxygen). When an active metal brazing material containing Ti (titanium), Ag (silver), Cu (copper) and Sn (tin) is used, the constituent elements derived from the active metal brazing material are Ti, Ag, Cu and Sn. Even the components of the nitride-based ceramic component or the active metal brazing material may have components that are not detected (below the detection limit) by TEM-EDX.
[0045] When the total amount of constituent elements other than carbon is set to 100 at%, in any five measurement regions, the average value of the oxygen content is preferably 1 at% or more, and the average value of the nitrogen content is preferably 20 at% or more. The titanium nitride layer 5 is a region where the total amount of titanium and nitrogen is 70 at% or more. Therefore, the ratio of constituent elements other than titanium and nitrogen in the titanium nitride layer 5 is less than 30 at%.
[0046] The amount of oxygen in the titanium nitride layer 5 is 1 at % or more. The amount of oxygen in a minute measurement region of 20 nm×20 nm in the titanium nitride layer 5 is 1 at % or more. This can improve the TCT characteristics.
[0047] The titanium nitride layer 5 is mainly formed by the reaction of the titanium of the brazing material and the nitrogen of the nitride-based ceramic. When a continuous furnace is used in the joining process, nitrogen from the nitrogen atmosphere is sometimes taken in to form the titanium nitride layer 5. The titanium nitride constituting the titanium nitride layer 5 is preferably a crystalline compound as the main body. Amorphous titanium nitride may also exist in the titanium nitride layer 5. The titanium nitride layer 5 may also be an aggregate of titanium nitride particles. The oxygen present in the titanium nitride layer 5 becomes oxygen dissolved in the titanium nitride crystal. The solid solution of oxygen into the titanium nitride crystal is substitutional or interstitial. In either case, there is an upper limit to the solid solution amount. That is, if the titanium nitride crystal has a certain solid solution amount, it becomes difficult for oxygen to be solid-dissolved in the titanium nitride crystal at a level exceeding the solid solution amount. In addition, oxygen may also exist in the grain boundaries of the titanium nitride crystal. By allowing the titanium nitride layer 5 to contain a specified amount of oxygen, the characteristics can be improved.
[0048] The results of the above-mentioned regional analysis are more preferably such that the average value of the nitrogen content in any five measurement regions is within a range of 50 at% or more and 65 at% or less, and the average value of the oxygen content is within a range of 1 at% or more and 10 at% or less. TiN is a compound in which the atomic ratio of Ti to N is 1:1. The nitrogen content in the titanium nitride layer 5 being 50 at% or more means that the titanium nitride layer 5 contains more nitrogen than TiN.
[0049] If the average value of the nitrogen content is less than 20at%, the reaction between the nitride-based ceramic component and Ti (Ti of the active metal brazing filler metal) may be insufficient. If the reaction is insufficient, the bonding strength may be reduced. If the average value of the nitrogen content exceeds 65at%, there may be too much nitrogen and the titanium nitride layer 5 may become unstable, thereby reducing the bonding strength. If the titanium nitride layer 5 becomes unstable, it may become difficult to maintain stable TiN crystals and Ti-NO compounds. In addition, there is a possibility that the reaction between the nitride-based ceramic component and Ti does not proceed well. Therefore, the average value of the nitrogen content is preferably within the range of 50at% to 65at%, more preferably within the range of 51at% to 62at%. In addition, if the average value of the oxygen content exceeds 10at%, the titanium nitride layer 5 may become unstable, thereby reducing the bonding strength. Therefore, the average value of the oxygen content is preferably within the range of 1at% to 10at%, more preferably within the range of 1.5at% to 7at%.
[0050] The results of the above regional analysis are preferably that in any of the five measurement regions, the nitrogen content is within the range of 50 at% or more and 65 at% or less, and the oxygen content is within the range of 1 at% or more and 10 at% or less. That is, in the region where the total amount of titanium and nitrogen in the titanium nitride layer 5 is 70 at% or more, the oxygen content in the measurement region of 20nm×20nm is preferably within the range of 1 at% or more and 10 at% or less. This means that titanium nitride in which oxygen is solid-dissolved exists in any micro-region. By having oxygen in any micro-region of 20nm×20nm, it is possible to further seek to improve the characteristics.
[0051] The titanium nitride layer 5 preferably comprises a Ti-NO compound. The Ti-NO compound is preferably a solid solution in which oxygen is dissolved in titanium nitride. The presence or absence of the Ti-NO compound can be determined by the above-mentioned TEM-EDX. The atomic ratio of Ti, N, and O in the Ti-NO compound is arbitrary. As an example of the Ti-NO compound, TiN 0.5 O 0.5 TiN x O (1-x) , 0.2≤x≤1.0. It is preferred that 90 atomic % or more of the Ti-NO compounds satisfying the above chemical formula exist in the Ti-NO compounds contained in the titanium nitride layer 5. In addition, the Ti-NO compound may contain components other than Ti, N and O as constituent elements, such as Ti-NO-Si.
[0052] It is believed that the detection of the Ti-NO compound can make the distribution of the oxygen amount more uniform. In addition, by forming the Ti-NO compound, the degradation of the titanium nitride layer 5 caused by oxidation can be suppressed. In other words, by the presence of the Ti-NO compound in advance, the titanium nitride layer can be suppressed from being newly oxidized. It should be noted that oxygen that does not constitute the Ti-NO compound may also exist in the titanium nitride layer 5.
[0053] In addition, the material constituting the titanium nitride layer 5 is preferably based on a space group Fm-3m structure having a sodium chloride structure (e.g., TiN: JCPDS card 00-038-1420, or Ti-NO JCPDS card 00-049-1325), and contains oxygen in a solid solution. The titanium nitride containing oxygen in a solid solution preferably has a plane spacing measured by TEM electron beam diffraction method that is wider than the plane spacing of the above card. For example, in the case of the (111) plane of the 00-038-1420TiN phase, the plane spacing is preferably 0.00001 / nm or more, and more preferably 0.001 / nm or more.
[0054] The thickness of the titanium nitride layer 5 is preferably in the range of 0.1 μm to 2 μm. When the thickness of the titanium nitride layer 5 is less than 0.1 μm, the bonding strength may be insufficient. If the titanium nitride layer 5 is thicker than 2 μm, the above effects may not be obtained. Therefore, the thickness of the titanium nitride layer 5 is preferably in the range of 0.1 μm to 2 μm, and more preferably in the range of 0.2 μm to 1 μm. It should be noted that the thickness of the titanium nitride layer 5 is the thickness on the straight line from the nitride-based ceramic substrate toward the copper plate.
[0055] The thickness of the bonding layer 4 is preferably within the range of 5 μm or more and 40 μm or less. When the thickness of the bonding layer 4 is less than 5 μm, the bonding strength may be insufficient. If the bonding layer 4 is thicker than 40 μm, the above effects may not be obtained. Therefore, the thickness of the bonding layer 4 is preferably within the range of 5 μm or more and 40 μm or less, and more preferably within the range of 10 μm or more and 30 μm or less.
[0056] The titanium nitride layer 5 may also have titanium nitride particles with an average particle size of less than 100 nm. The titanium nitride particles may also be Ti-NO compound particles. The presence of titanium nitride particles makes it easier to control the distribution of the amount of oxygen. Therefore, the average particle size of the titanium nitride particles is preferably less than 100 nm, and more preferably less than 20 nm. The lower limit of the average particle size of the titanium nitride particles is not particularly limited, but is preferably greater than 5 nm. When the average particle size is less than 5 nm, the thickness of the titanium nitride layer may be insufficient. Therefore, the average particle size of the titanium nitride particles is preferably within the range of greater than 5 nm and less than 100 nm, and more preferably within the range of greater than 10 nm and less than 20 nm. It should be noted that the average particle size of the titanium nitride particles is measured by TEM observation. The major diameter of the titanium nitride particles is measured by TEM observation, and the average value of the major diameters of any 20 particles is taken as the average particle size.
[0057] The bonding layer 4 preferably contains Ti, at least one selected from the group consisting of Cu and Ag, and at least one selected from the group consisting of Sn, In and C. The bonding layer 4 includes a titanium nitride layer 5. The titanium nitride layer 5 is a region where the total of titanium and nitrogen is more than 70at%. Between the titanium nitride layer 5 and the copper component, a region where the total of titanium and nitrogen is less than 70at% is formed. In the region where the total of titanium and nitrogen is less than 70at%, it is preferred to include at least one selected from the group consisting of Cu and Ag and at least one selected from the group consisting of Sn, In and C. These elements contribute to improving the bonding strength with the copper component. In addition, when the joint body is used for a ceramic circuit substrate, the region of the bonding layer 4 containing these elements can also be used for the bonding layer extension. By forming the bonding layer extension, the TCT characteristics can be improved.
[0058] Ti, at least one selected from the group consisting of Cu and Ag, and at least one selected from the group consisting of Sn, In, and C are preferably added as components of the active metal brazing filler metal. By using an active metal brazing filler metal containing these elements, a bonding layer 4 containing Ti, at least one selected from the group consisting of Cu and Ag, and at least one selected from the group consisting of Sn, In, and C can be obtained.
[0059] As components of the active metal brazing filler metal, Ti (titanium) or TiH2 (titanium hydride) of 1 mass % to 15 mass %, Cu (copper) of 15 mass % to 85 mass %, Ag (silver) of 0 mass % to 70 mass %. It is also possible to include one or more selected from Sn (tin) and In (indium) in a range of 1 mass % to 50 mass %, and C (carbon) in a range of 0.1 mass % to 2 mass %.
[0060] Ti (titanium) is a component that reacts with the nitride-based ceramic component to form the titanium nitride layer 5. Ti can also be added as TiH2 (titanium hydride). The content of Ti or TiH2 is preferably in the range of 5% by mass or more and 15% by mass or less. By increasing the amount of Ti to 5% by mass or more, it becomes easier to take in oxygen in the titanium nitride layer.
[0061] Cu and Ag are main components of the bonding layer 4. When both Ag and Cu are used, the content of Ag is preferably in the range of 20 mass % to 60 mass %, and the content of Cu is preferably in the range of 15 mass % to 40 mass %. The active metal brazing filler metal may not contain Ag.
[0062] Sn and In have the effect of lowering the melting point of the solder. In addition, Sn and In have the effect of improving TCT characteristics by alloying with Cu. Carbon is a component for controlling the fluidity of the solder. Control of the fluidity of the solder is effective for uniform dispersion of the solder components.
[0063] In the active metal brazing filler metal, one or more selected from tungsten (W), molybdenum (Mo) and rhenium (Re) may be added in a range of 0.1 mass % to 10 mass %. By adding one or more of carbon, tungsten, molybdenum and rhenium, the fluidity of the active metal brazing filler metal can be controlled. Magnesium (Mg) may also be added to the active metal brazing filler metal.
[0064] The content of the brazing material component is calculated by setting the total of the constituent components of the brazing material to 100 mass %. The binder, solvent, etc. used for preparing the brazing material paste are not included in the content of the brazing material component.
[0065] By using active metal brazing filler metals, such as Figure 2As shown in FIG. 1 , a titanium nitride layer 5 and a brazing material layer 7 are formed in the bonding layer 4. The brazing material layer 7 is a region in which the total amount of titanium and nitrogen in the bonding layer 4 is less than 70 at%, and is located between the titanium nitride layer 5 and the metal member 3. In the brazing material layer 7, a Ti-rich region 9 may also exist. The main component of the brazing material layer 7 is a component of the active metal brazing material. Therefore, titanium components are also distributed in the brazing material layer 7. The titanium component in the brazing material layer 7 is titanium that has not become the titanium nitride layer 5.
[0066] The bonding layer 4 has a titanium nitride layer 5 and a brazing material layer 7. When the brazing material layer 7 is analyzed, it includes a Ti-rich region 9 containing 30 at% or more of Ti. The amount of nitrogen in the Ti-rich region 9 is preferably in the range of 1 at% or more and 15 at% or less. It should be noted that the brazing material layer 7 may also include a region other than the Ti-rich region 9. For example, the brazing material layer 7 may also include a Ti-poor region containing 0 at% or more and less than 30 at% of Ti.
[0067] Analysis using TEM-EDX can be used for the analysis of the brazing material layer 7. Specifically, first, the brazing material layer 7 is subjected to surface analysis by EDX. From the result of the surface analysis, the region containing 30 at% or more of Ti is determined as the Ti-rich region 9. A measurement region is set in the determined Ti-rich region 9, and by analyzing the measurement region with TEM-EDX, the content of the elements contained in the Ti-rich region 9 can be measured. The size of the measurement region is set to 20 nm×20 nm, for example.
[0068] The amount of nitrogen in the Ti-rich region 9 of the brazing material layer 7 is less than the amount of nitrogen in the titanium nitride layer 5. Thus, the TCT characteristics can be improved. In addition, the amount of oxygen in the Ti-rich region 9 is preferably in the range of 0 at% or more and 3 at% or less. By reducing the amount of oxygen in the Ti-rich region 9, the amount of oxygen in the titanium nitride layer 5 can be controlled within a prescribed range. In other words, by setting the amount of oxygen in the titanium nitride layer 5 within a prescribed range, the amount of oxygen in the Ti-rich region 9 can be reduced.
[0069] The Ti-rich region 9 is composed of Ti and active metal brazing components other than Ti. For example, when a CuSnTi-based brazing material is used as an active metal brazing material, the Ti-rich region 9 may also contain one or two of Cu and Sn. The upper limit of the amount of Ti in the Ti-rich region 9 is not particularly limited, but is preferably 50 at% or less. If the amount of Ti exceeds 50 at%, the proportion of components other than Ti in the active metal brazing material decreases. Therefore, the amount of Ti in the Ti-rich region 9 is preferably in the range of 30 at% or more and 50 at% or less, and more preferably in the range of 33 at% or more and 46 at% or less.
[0070] The Ti-rich region 9 preferably contains one selected from Sn or In in the range of 20 at% to 40 at%. In addition, the Ti-rich region 9 preferably contains Cu in the range of 0 at% to 20 at%. In the Ti-rich region, when the sum of the contents of Ti, Sn, Cu, N and O is set to 100 at%, the Ti content is preferably 30 at% to 50 at%, the Sn content is 20 at% to 40 at%, the Cu content is 0 at% to 20 at%, the nitrogen content is 1 at% to 15 at%, and the oxygen content is 0 at% to 3 at%. The fact that the Ti-rich region 9 satisfies this composition range indicates that the main component of the Ti-rich region 9 is the SnTi alloy phase. That is, nitrogen exists in the SnTi alloy phase. When In is used instead of Sn, Sn is replaced by In. That is, the main component of the Ti-rich region 9 becomes the InTi alloy phase.
[0071] The area ratio of the Ti-rich region 9 is preferably within a range of 5% or more and 30% or less of the bonding layer 4. For the measurement of the area ratio of the Ti-rich region 9, SEM-EDX is used. As SEM, Field Emission SEM (FE-SEM) can also be used. As FE-SEM, JSM-7200F manufactured by JEOL or an apparatus having equivalent performance is used. As EDX, EX-74600U4L2Q manufactured by JEOL or an apparatus having equivalent performance is used.
[0072] Here, a joint body in which a copper component is used as a metal component 3 and a nitride-based ceramic substrate is used as a nitride-based ceramic component 2 is described as an example. As far as FE-SEM is concerned, an arbitrary cross section of the bonding layer 4 is observed. The cross section is a plane parallel to the thickness direction. The thickness direction is perpendicular to the surface of the nitride-based ceramic substrate and parallel to the direction in which the nitride-based ceramic substrate is connected to the copper component. The measurement conditions of FE-SEM are set to an acceleration voltage of 15 kV and a magnification of 3000 times. The field of view area is set to the thickness of the bonding layer × 40 μm in the width direction. For example, when the thickness of the bonding layer 4 is 30 μm, the field of view area is set to 30 μm in the thickness direction × 40 μm in the width direction. The width direction is parallel to the surface of the nitride-based ceramic substrate and perpendicular to the thickness direction.
[0073] The measurement conditions of EDX are set to 50 scans and a dwell time of 0.2ms. The dwell time is the measurement speed per pixel. When performing regional analysis of EDX, the number of captured pixels is set to 256 pixels horizontally and 198 pixels vertically, the number of detection counts is 3700 to 4100 cps (Count Per Second), and the quantitative map is 5×5 bit / point. Point analysis is an analysis of the measurement results using 1 detection count (1 place). Regional analysis is an analysis of the measurement results using multiple detection counts. Regional analysis is sometimes also called surface analysis.
[0074] The analysis using EDX can also be performed after the elements constituting the bonding layer 4 are investigated in advance and the specific elements are identified. For example, when Cu (copper), Sn (tin), Ti (titanium), Si (silicon), O (oxygen), and N (nitrogen) are detected as elements constituting the bonding layer 4, these elements are set as specific elements. The results of regional analysis are used to map specific elements. For example, the titanium nitride layer 5 in the bonding layer 4 is determined by the results of the mapping of Ti and N. As described above, the area in which the total amount of titanium and nitrogen is greater than 70at% and less than 100at%, and is connected to the surface direction of the nitride-based ceramic component 2 for more than 5μm is determined to be the titanium nitride layer 5. The area other than the titanium nitride layer 5 in the bonding layer 4 is the brazing layer 7. The Ti-rich region 9 is determined by the mapping results of Ti in the brazing layer 7. By measuring the area of the bonding layer 4 and the area of the Ti-rich region 9, the area ratio of the Ti-rich region 9 can be calculated. For the mapping of SEM-EDX, the attached function in SEM-EDX is used. In the absence of an attached mapping function, image software is used for mapping.
[0075] The area ratio is calculated by performing regional analysis on three regions using EDX and using the average value. The area of one region (field of view area) is the thickness of the bonding layer × 40 μm in the width direction. The field of view corresponds to the bonding layer 4. From the cross section of the bonding layer 4, any three adjacent regions are selected and each of the three regions is analyzed. The bonding layer 4 is the range from the boundary between the nitride-based ceramic substrate and the bonding layer 4 to the boundary between the bonding layer 4 and the copper component.
[0076] The boundary between the nitride-based ceramic substrate and the bonding layer 4 is the bonding interface between the surface of the nitride-based ceramic substrate and the titanium nitride layer 5. For example, when a silicon nitride substrate is used, the bonding interface between the silicon nitride substrate and the titanium nitride layer is the boundary between the nitride-based ceramic substrate and the bonding layer 4. The boundary between the bonding layer 4 and the copper component is defined based on the amount of Ti. Near the boundary between the bonding layer 4 and the copper component, the amount of Ti gradually decreases from the bonding layer 4 toward the surface of the copper component. The boundary is defined based on a region where the amount of Ti is less than 1 atomic % and a 50 μm portion is continuously formed in the width direction. When there are multiple such portions, the boundary between the bonding layer 4 and the copper component is defined based on the portion closest to the bonding layer 4 (nitride-based ceramic substrate) among the multiple portions.
[0077] In the bonded body, copper plates may be bonded to both surfaces of the nitride-based ceramic member via bonding layers. When copper plates are bonded to both surfaces, the titanium nitride layers 5 on both surfaces preferably have the above-mentioned properties.
[0078] The bonded body of the embodiment can be used for a ceramic circuit board. Figure 3 1 is a side view showing an example of a ceramic circuit substrate according to an embodiment of the present invention. Figure 3 In the figure, symbol 10 is a ceramic circuit substrate, symbol 11 is a circuit portion (front copper plate), and symbol 12 is a heat sink (back copper plate). The circuit portion 11 can be obtained by giving a circuit shape to a metal component. Alternatively, the metal component processed into a circuit shape can be joined to the nitride-based ceramic component 2 to obtain a ceramic circuit substrate 10.
[0079] Figure 3 The ceramic circuit substrate 10 shown in the example has two circuit sections 11. Three or more circuit sections 11 may be provided on the nitride-based ceramic member 2. Figure 3 In the example shown in , a circuit portion 11 is provided on the surface of the nitride-based ceramic component 2, and a heat sink 12 is provided on the back surface. This example is not limited thereto, and the circuit portion 11 may be provided on both sides of the nitride-based ceramic component 2. As required, an inclined shape may be provided on the side surface of the circuit portion 11 and the side surface of the heat sink 12. In addition, as required, an extension portion extending from the end of the circuit portion 11 or the end of the heat sink 12 may also be provided in the bonding layer 4.
[0080] Figure 4 This is a side view showing an example of a semiconductor device according to an embodiment. Figure 4 In the figure, reference numeral 10 is a ceramic circuit substrate, reference numeral 14 is a semiconductor element, and reference numeral 20 is a semiconductor device. The semiconductor device 20 can be obtained by mounting the semiconductor element 14 in the circuit portion 11. When manufacturing the semiconductor device 20, metal terminals, wire bonding, or resin sealing may be provided as required.
[0081] The ceramic circuit board 10 of the embodiment has good TCT characteristics. In recent years, the junction temperature has increased along with the performance improvement of the semiconductor element 14. In SiC elements, the junction temperature is set to be around 200°C.
[0082] The conjugate 1 of the embodiment suppresses degradation caused by further oxidation of the titanium nitride layer 5. Oxidation easily occurs in a high temperature environment or an environment with high humidity. According to the embodiment, oxidation of the titanium nitride layer 5 caused by high temperature or moisture can be suppressed. For example, semiconductor devices used in automobiles or industrial equipment are sometimes used in an environment with high humidity in addition to the heat generated by the semiconductor elements. Therefore, degradation caused by further oxidation is more likely to occur. According to the embodiment, since degradation caused by oxidation of the titanium nitride layer can be suppressed, the conjugate can be used in various environments.
[0083] Next, a method for producing the bonded body of the embodiment will be described. The method for producing the bonded body of the embodiment is not particularly limited as long as it has the above-mentioned structure. Here, an example of a method for obtaining the bonded body of the embodiment with a good yield will be described.
[0084] First, a nitride-based ceramic component is prepared. The nitride-based ceramic component is preferably a silicon nitride substrate or an aluminum nitride substrate. In addition, a copper plate is prepared as a metal component. The copper plate is preferably an oxygen-free copper plate or a copper alloy plate.
[0085] Next, an active metal brazing filler metal is prepared. The active metal brazing filler metal preferably comprises Ti, at least one selected from the group consisting of Cu and Ag, and at least one selected from the group consisting of Sn, In and C. As Ti, a single substance of Ti may be added, or TiH2 (titanium hydride) may be added. The mixing ratio of each element in the active metal brazing filler metal is as described above. After mixing each brazing filler metal component, an adhesive or the like is added to the mixture to prepare an active metal brazing filler metal paste. The adhesive is, for example, an organic adhesive.
[0086] An active metal brazing material layer is formed by applying an active metal brazing material paste on a nitride-based ceramic component. A copper plate is arranged on the active metal brazing material layer. When copper plates are bonded to both sides of a nitride-based ceramic component, an active metal brazing material layer is also formed on the other side, and a copper plate is arranged thereon. An object in which an active metal brazing material layer and a copper plate are arranged on a nitride-based ceramic component is called a laminate.
[0087] A process of heat-joining the stacked body is performed. A joint body is produced by heat-joining the stacked body. In addition, the active metal brazing material layer becomes a joining layer by heat-joining. In the heat-joining process, a continuous furnace is preferably used. A continuous furnace is a furnace that heats the heated object while transporting it. For example, in International Publication No. 2022 / 244769 (Patent Document 5), a method for manufacturing a joint body using a continuous furnace is disclosed. According to the invention described in Patent Document 5, by controlling the heating rate and the cooling rate, a joint body can be obtained with a good yield.
[0088] In order to control the amount of oxygen in the titanium nitride layer, it is effective to control the amount of oxygen in the atmosphere during the heating and bonding process. A continuous furnace is used in the heating and bonding process. In the continuous furnace, a nitrogen atmosphere is controlled. The oxygen concentration in the nitrogen atmosphere is preferably in the range of 10 volppm or more and 1000 volppm or less. By controlling the amount of oxygen in the nitrogen atmosphere, oxygen is taken into the titanium nitride layer formed in the heating process. If the oxygen concentration is lower than 10 volppm, there is a possibility that there is insufficient oxygen in the titanium nitride layer. In addition, if the oxygen concentration exceeds 1000 volppm, it becomes easy to form a region where the total amount of titanium and nitrogen is less than 70 at%. Therefore, the amount of oxygen in the nitrogen atmosphere is preferably in the range of 10 volppm or more and 1000 volppm or less, and more preferably in the range of 50 volppm or more and 200 volppm or less. In order to control the amount of oxygen in the nitrogen atmosphere, oxygen gas may be supplied in addition to nitrogen as needed.
[0089] The concentration of carbon monoxide (CO) in the nitrogen atmosphere is preferably 1000 volppm (0.1 vol%) or less. CO has reducing properties. Therefore, CO may inhibit the uptake of oxygen into titanium nitride. The concentration of CO is preferably 1000 volppm or less, and more preferably 100 volppm or less.
[0090] As described above, an organic binder is added to the active metal brazing paste. In the heating and joining process, CO gas is sometimes generated when the organic binder gradually disappears. The continuous furnace is suitable for mass production because it can continuously process the joined bodies. In order to prevent the CO gas generated by the joined bodies from remaining, it is effective to exhaust the space inside the continuous furnace.
[0091] When the heating and joining zone of the continuous furnace is fully exhausted, the amount of oxygen in the nitrogen atmosphere becomes substantially equal to the amount of oxygen contained in the nitrogen gas supplied to the heating and joining zone. Similarly, the amount of CO in the nitrogen atmosphere becomes substantially equal to the amount of CO contained in the nitrogen gas supplied to the heating and joining zone. Therefore, it is preferred that the amount of oxygen in the nitrogen gas supplied to the heating and joining zone is within a range of 10 volppm or more and 1000 volppm or less, and the amount of CO in the nitrogen gas is 1000 volppm or less.
[0092] The continuous furnace heats and bonds the laminated body while conveying it. The interior of the continuous furnace is divided into a plurality of treatment zones corresponding to the temperature zones. For example, a plurality of treatment zones such as a normal temperature zone, a temperature rising zone, a heating and bonding zone, and a temperature falling zone are provided. The normal temperature zone is the zone where the laminated body is started to be conveyed into the continuous furnace. In addition, in the temperature rising zone, the temperature of the laminated body gradually rises to the bonding temperature in stages. In the heating and bonding zone, the temperature of the laminated body is maintained at the heating temperature. In the temperature falling zone, the temperature of the laminated body gradually decreases in stages. In the temperature rising zone, the average heating rate from 200°C to the bonding temperature is preferably within the range of 15°C / minute or more and 200°C / minute or less. In the temperature falling zone, the average cooling rate from the bonding temperature to 200°C is preferably within the range of 15°C / minute or more and 200°C / minute or less.
[0093] For example, when the joining temperature is within the range of 650°C to 980°C, in the heated joining zone, the temperature of the stack is maintained within the range of 650°C to 980°C. At this time, it is effective to supply nitrogen gas with a controlled oxygen content to the heated joining zone. In addition, the oxygen content of the nitrogen gas supplied to the temperature rising zone can also be controlled. If heating is gradually performed in a continuous furnace, gas is generated when the adhesive is removed from the brazing material layer. By exhausting the temperature rising zone while supplying nitrogen gas with a controlled oxygen content, the effect of the gas generated by the brazing material layer on the oxygen concentration in the titanium nitride layer 5 can be reduced.
[0094] In the heating and joining area, the nitrogen flow rate is preferably more than 2 liters / minute. When heating and joining are performed, gases such as CO, hydrocarbons (CH series) are generated from the solder layer. By controlling the nitrogen flow rate, the gas generated from the solder layer can be removed without stagnation. Therefore, the nitrogen flow rate is preferably more than 2 liters / minute, more preferably more than 30 liters / minute. The upper limit of the nitrogen flow rate is not particularly limited, but is preferably less than 400 liters / minute. If it exceeds 400 liters / minute, then due to the excessive wind volume, it is possible to become the cause of the misalignment of the stacked body being transported. Therefore, the nitrogen flow rate is preferably within the range of more than 2 liters / minute and less than 400 liters / minute, more preferably within the range of more than 30 liters / minute and less than 300 liters / minute.
[0095] The nitrogen flow rate supplied to the temperature rising zone is preferably controlled in the same manner. Since the organic binder also volatilizes in the temperature rising zone, CO, hydrocarbon and other gases are generated. The nitrogen flow rate in the temperature falling zone is preferably controlled in the same manner. Immediately after the bonding zone is heated, the titanium nitride layer 5 may be affected by CO, hydrocarbon and other gases generated by the volatilization of the organic binder.
[0096] In the cooling zone, it is preferred to control the conveying speed of the stack. The conveying speed in the cooling zone from 650°C to 400°C is preferably in the range of 1 cm / minute to 15 cm / minute. For example, the conveying speed in the cooling zone from 400°C to 200°C may also be in the range of 15 cm / minute to 100 cm / minute. That is, in the cooling zone, the conveying speed in a specified temperature range is slower than that in other temperature ranges. In the cooling zone, the conveying speed may be increased at a temperature below 400°C because the effect on the bonded body is small. It should be noted that the conveying speed may be slowed down, but since the total processing time becomes longer, it cannot be said that the productivity is good.
[0097] In the joining process using active metal brazing filler metal, the active metal brazing filler metal gradually melts in the temperature rising zone. Along with the melting, the active metal brazing filler metal reacts with the nitride-based ceramic component to form a titanium nitride layer. In the temperature dropping zone, the joining layer including the titanium nitride layer solidifies. By slowing down the conveying speed in the process of solidifying the titanium nitride layer, oxygen becomes easier to be taken into the titanium nitride layer. As described above, oxygen is taken into the titanium nitride layer in the heating joining process. If excessive oxygen is taken in in the temperature rising zone, it may have an adverse effect on the joining. In the temperature dropping zone, since it is the stage of solidification of the joining layer, the intake of oxygen beyond necessity can be suppressed. It should be noted that when it is less than 1 cm / min (including 0 cm / min), the conveying speed may be too slow, and the contact time with oxygen in the nitrogen atmosphere becomes longer.
[0098] In addition, as long as the temperature of the stack can be controlled, the conveying speed outside the temperature drop zone is arbitrary. The conveying speed may also be within the range of 1 cm / minute or more and 15 cm / minute or less, or may exceed 15 cm / minute. The upper limit of the conveying speed is not particularly limited, but is preferably 30 cm / minute or less. If the conveying speed exceeds 30 cm / minute, it is necessary to extend the temperature rise zone and the heating bonding zone. This will cause the large-scale continuous furnace, so it is not preferred.
[0099] The amount of oxygen in the titanium nitride layer can be controlled by the amount of oxygen in the nitrogen atmosphere, the amount of carbon monoxide in the nitrogen atmosphere, the flow rate of nitrogen gas, the conveying speed, etc. Only one of these conditions can be used, or multiple conditions can be combined. By combining multiple conditions, it becomes easier to control the amount of oxygen in the titanium nitride layer.
[0100] Through the above steps, a joint body can be obtained. Afterwards, by giving a circuit shape to the copper plate of the joint body, a ceramic circuit substrate can be obtained. The process of giving the circuit shape preferably uses an etching process. In addition, a laminate can also be made using a copper plate that has been given a circuit shape in advance. In the case where an inclined shape is given to the side of the copper plate or an extension is formed in the joint layer, an etching process is also effective. From the aspect of giving an inclined shape and forming an extension, the process of giving a circuit shape is also preferably an etching process.
[0101] (Example)
[0102] (Examples 1 to 6, Comparative Examples 1 to 4)
[0103] As nitride-based ceramic components, silicon nitride substrates and aluminum nitride substrates were prepared. The thermal conductivity of the silicon nitride substrate was 90 W / m·K. The 3-point bending strength was 600 MPa. The dimensions were 200 mm in length × 150 mm in width × 0.32 mm in thickness. The thermal conductivity of the aluminum nitride substrate was 170 W / m·K. The 3-point bending strength was 400 MPa. The dimensions were 150 mm in length × 100 mm in width × 0.635 mm in thickness. An oxygen-free copper plate was used as the copper plate. The thickness of the copper plate is as shown in Table 1. In addition, the active metal brazing material shown in Table 2 was prepared.
[0104] Table 1
[0105] thickness Copper Plate 1 0.6mm Copper Plate 2 0.8mm Copper Plate 3 0.3mm
[0106] Table 2
[0107] Active metal brazing filler metal Composition (mass %) Brazing material 1 Ag(45), Cu(35), Sn(15), Ti(5) Brazing material 2 Ag(43.9), Cu(37), Sn(10), Ti(9), C(0.1) Brazing material 3 Cu(70), Sn(22), Ti(8) Brazing material 4 Cu(67.9), Sn(26), Ti(6), C(0.1) Brazing material 5 Ag(55), Cu(35), Sn(8), Ti(2)
[0108] An active metal brazing material paste is prepared by adding a binder and the like to the active metal brazing material. The active metal brazing material paste is applied to both sides of the silicon nitride substrate to form an active metal brazing material layer. A copper plate is arranged on each active metal brazing material layer. Through these steps, a laminate is prepared. The laminate comprises a silicon nitride substrate, active metal brazing material layers formed on both sides thereof, and copper plates arranged on each active metal brazing material layer. The combination of the laminate is as shown in Table 3.
[0109] Table 3
[0110]
[0111] Next, in Examples 1 to 6 and Comparative Examples 1 and 3, the laminated bodies were heat-bonded using a continuous furnace to obtain bonded bodies. In Comparative Examples 2 and 4, the laminated bodies were heat-bonded using a vacuum furnace (intermittent furnace) to obtain bonded bodies.
[0112] In the continuous furnace, the bonding temperature of the heating bonding zone is set to a range of 750°C to 980°C. The heating rate from 200°C to the bonding temperature is set to 20°C / min. The cooling rate from the bonding temperature to 200°C is set to 20°C / min. The characteristics of the nitrogen supplied to the heating bonding zone are as shown in Table 4. In the embodiment, the nitrogen flow rate in each of the heating zone, the heating bonding zone and the cooling zone is set to a range of 30 liters / min to 300 liters / min to 300 liters / min. In the embodiment, the conveying speed in the cooling zone is set to a range of 1 cm / min to 15 cm / min to 15 cm / min. In Comparative Examples 1 and 3, the nitrogen flow rate in each of the heating zone, the heating bonding zone and the cooling zone is set to 1 liter / min. In Comparative Examples 1 and 3, the conveying speed in the cooling zone is set to 35 cm / min. In Comparative Examples 2 and 4, an intermittent furnace is used to heat the bonding zone at a bonding temperature of 850°C and in a vacuum (10 -3 Pa or less) for bonding.
[0113] Table 4
[0114]
[0115] Through the above steps, the joint bodies of the embodiment and the comparative example were obtained. Next, the cross section of the joint body was analyzed by TEM-EDX. In the joint bodies of the embodiment and the comparative example, a titanium nitride layer with titanium nitride as the main component was observed. That is, a region was observed in which the total content of titanium and nitrogen was more than 70 at% and was connected to the surface direction of the nitride-based ceramic substrate for more than 5 μm.
[0116] Next, in each of the embodiments and comparative examples, any five 20 nm × 20 nm measurement areas separated from each other are selected from the titanium nitride layer. Each selected measurement area is subjected to regional analysis by TEM-EDX. In each embodiment and comparative example, the average value of the nitrogen content in the five measurement areas, the average value of the oxygen content in the five measurement areas, and the minimum and maximum values of the oxygen content in the five measurement areas are obtained. The oxygen content and nitrogen content are calculated by setting the total of the constituent elements other than carbon to 100 at%. In addition, the thickness of the titanium nitride layer and the presence or absence of Ti-NO compounds are measured. The results are shown in Table 5.
[0117] Table 5
[0118]
[0119] As can be seen from Table 5, in the example, the average value of the nitrogen content is within the range of 50 at% to 65 at%. Moreover, the average value of the oxygen content is within the range of 1 at% to 10 at%. In addition, the minimum and maximum values of the oxygen content in the five measurement areas are within the range of 1 at% to 10 at%. From this result, it can be seen that in the example, oxygen is distributed in the titanium nitride layer.
[0120] In contrast, in Comparative Example 1, the average value of the oxygen content was less than 1 at%. In addition, the minimum value of the oxygen content in the five measurement areas was less than 0.1 at%. That is, in Comparative Example 1, there was a portion in the titanium nitride layer where the oxygen content was less than 1 at%. In Comparative Example 2, no oxygen content was detected in the titanium nitride layer. This is because a vacuum furnace (intermittent furnace) was used. In an intermittent furnace, since the titanium nitride layer is heated in a vacuum (10 -3 Pa or less) is processed, so oxygen is not taken into the titanium nitride layer.
[0121] In addition, in the embodiment, a Ti-rich region is confirmed in the brazing material layer. In the Ti-rich region, the Ti content is in the range of 30 at% to 50 at%, the nitrogen content is in the range of 1 at% to 15 at%, the oxygen content is in the range of 0 at% to 3 at%, the Sn content is in the range of 20 at% to 40 at%, and the Cu content is in the range of 0 at% to 20 at%. These proportions are calculated by setting the sum of the contents of Ti, Sn, Cu, N and O to 100 at%. In addition, the area ratio of the Ti-rich region in the bonding layer is in the range of 5% to 30%. In contrast, in the comparative example, no Ti-rich region was observed. It should be noted that the analysis method of the Ti-rich region is as described above.
[0122] Next, the bonded body was subjected to etching treatment to produce a ceramic circuit board. The shape of the circuit portion, the shape of the extended portion of the bonding layer, etc. were common in the examples and comparative examples. The obtained ceramic circuit board was subjected to a TCT test.
[0123] In the test, multiple conditions were used. The first test A was performed on a ceramic circuit substrate using the silicon nitride substrate of Examples 1 to 4 and Comparative Examples 1 to 2. The first test B was performed on a ceramic circuit substrate using the aluminum nitride substrate of Examples 5 to 6 and Comparative Examples 3 to 4. In the first test A, -40°C × 30 minutes, room temperature × 10 minutes, 200°C × 30 minutes, and room temperature × 10 minutes were set as one cycle, and the presence of defects in the ceramic circuit substrate after 3000 cycles was measured. In the first test B, -20°C × 30 minutes, room temperature × 10 minutes, 125°C × 30 minutes, and room temperature × 10 minutes were set as one cycle, and the presence of defects in the ceramic circuit substrate after 1500 cycles was measured.
[0124] Furthermore, the second test was performed on the ceramic circuit substrates of each of the examples and comparative examples. In the second test, the sample before the TCT test was placed in an environment of temperature 85°C and humidity 85% for 20 hours, and then the TCT test was performed. The conditions of the TCT test were the same as those of the first test. That is, the first test A was performed on the ceramic circuit substrates of Examples 1 to 4 and Comparative Examples 1 to 2. The first test B was performed on the ceramic circuit substrates of Examples 5 to 6 and Comparative Examples 3 to 4.
[0125] The presence or absence of defects in the ceramic circuit substrate is evaluated by measuring the crack generation area between the ceramic substrate and the metal plate. For the measurement of the crack generation area, an ultrasonic flaw detector (Scanning Acoustic Tomograh: SAT) was used. The results are shown in Table 6. In Table 6, the index Itar (η) represents the ratio of the crack generation area to the bonding area between the ceramic substrate and the metal plate. For example, when Itar (η) is 100%, it means that no cracks have occurred, and when Itar (η) is 0%, it means that cracks have occurred on the entire surface.
[0126] Table 6
[0127]
[0128] As can be seen from Table 6, in the first test, no adverse conditions were confirmed in either the example or the comparative example. In the second test, no adverse conditions were confirmed for the example. In contrast, for the comparative example, η decreased compared to the result of the first test, and an adverse condition was confirmed. This is believed to be because the titanium nitride layer was oxidized while the ceramic circuit substrate was placed in a high-temperature, high-humidity environment. From the test results, it can be seen that the ceramic circuit substrate of the example is a ceramic circuit substrate that is resistant to easily oxidized atmospheres such as high temperature and high humidity. Therefore, the ceramic circuit substrate of the example is effective for semiconductor devices used in high-temperature or high-humidity environments.
[0129] The embodiments of the present invention include the following features.
[0130] (Feature 1) A joined body comprising a nitride-based ceramic component and a metal component joined to the nitride-based ceramic component via a joining layer,
[0131] A titanium nitride layer containing titanium nitride as a main component is formed at the interface between the nitride-based ceramic member and the bonding layer.
[0132] The titanium nitride layer includes a portion having an oxygen content of 1 at % or more.
[0133] (Feature 2) The conjugate according to Feature 1, wherein
[0134] The amount of nitrogen in the above-mentioned portion of the above-mentioned titanium nitride layer is 20 at % or more.
[0135] (Feature 3) The conjugate according to Feature 1 or Feature 2, wherein:
[0136] A 20 nm×20 nm measurement area in the titanium nitride layer was subjected to regional analysis by TEM-EDX, and when the total amount of constituent elements other than carbon was set to 100 at %,
[0137] The average value of the oxygen content in any five of the above measurement areas is 1 a t% or more,
[0138] The average value of the nitrogen content in the five measurement areas is 20 at % or more.
[0139] (Feature 4) The conjugate according to Feature 3, wherein:
[0140] The above average value of the above oxygen content is within the range of 1 at % to 10 at %,
[0141] The average value of the nitrogen amount is within a range of 50 at % to 65 at %.
[0142] (Feature 5) The conjugate according to Feature 4, wherein
[0143] In any of the five measurement regions, the nitrogen amount is within a range of 50 at % to 65 at %, and the oxygen amount is within a range of 1 at % to 10 at %.
[0144] (Feature 6) The conjugate according to any one of Features 1 to 5, wherein
[0145] The above-mentioned bonding layer contains:
[0146] Ti,
[0147] At least one selected from the group consisting of Cu and Ag, and
[0148] At least one selected from the group consisting of Sn, In, and C.
[0149] (Feature 7) The conjugate according to any one of Features 1 to 6, wherein
[0150] The above-mentioned bonding layer comprises:
[0151] The titanium nitride layer and
[0152] a brazing material layer between the titanium nitride layer and the metal component,
[0153] The brazing material layer includes a Ti-rich region containing 30 at % or more of Ti.
[0154] The amount of nitrogen in the Ti-rich region is within a range of 1 at % to 15 at %.
[0155] (Feature 8) The conjugate according to Feature 7, wherein:
[0156] When a measurement region of 20 nm×20 nm in the brazing material layer was analyzed by TEM-EDX, the measurement region included the Ti-rich region.
[0157] (Feature 9) The conjugate according to Feature 7 or Feature 8, wherein
[0158] When observing the bonding layer in an arbitrary cross section, the area ratio of the Ti-rich region in the bonding layer is within a range of 5% to 30%.
[0159] (Feature 10) The conjugate according to any one of Features 1 to 9, wherein
[0160] The thickness of the titanium nitride layer is within a range of 0.1 μm to 2 μm.
[0161] (Feature 11) The conjugate according to any one of Features 1 to 10, wherein
[0162] The metal members are bonded to both surfaces of the nitride-based ceramic member via the bonding layers.
[0163] (Feature 12) A ceramic circuit substrate,
[0164] The conjugate comprises any one of Features 1 to 11,
[0165] The nitride-based ceramic component has a substrate shape.
[0166] The metal member has a circuit shape.
[0167] (Feature 13) A joined body comprising a nitride-based ceramic component and a metal component joined to the nitride-based ceramic component via a joining layer,
[0168] The bonding layer includes a Ti-rich region,
[0169] In the Ti-rich region, when the sum of the Ti content, the Sn content, the Cu content, the nitrogen content, and the oxygen content is set to 100 at%, the Ti content is 30 at% to 50 at%, the Sn content is 20 at% to 40 at%, the Cu content is 0 at% to 20 at%, the nitrogen content is 1 at% to 15 at%, and the oxygen content is 0 at% to 3 at%.
[0170] The area ratio of the Ti-rich region is in the range of 5% to 30%.
[0171] Several embodiments of the present invention are illustrated above, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, changes, etc. can be made without departing from the scope of the main purpose of the invention. These embodiments and their modifications are included in the scope and main purpose of the invention, and are also included in the invention described in the claims and their equivalents. In addition, the above-mentioned embodiments can be implemented in combination with each other.
[0172] Explanation of symbols
[0173] 1…joint
[0174] 2…Nitride-based ceramic substrate
[0175] 3…Copper components
[0176] 4…Joint layer
[0177] 5…Titanium nitride layer
[0178] 6…Measurement area
[0179] 7…Braze layer
[0180] 9…Ti-rich areas
[0181] 10…Ceramic circuit substrate
[0182] 11…Circuit Board
[0183] 12…Heat Radiator
[0184] 14…Semiconductor components
[0185] 20…Semiconductor devices
Claims
1. A joined body comprising a nitride-based ceramic component and a metal component joined to the nitride-based ceramic component via a joining layer, A titanium nitride layer containing titanium nitride as a main component is formed at the interface between the nitride-based ceramic member and the bonding layer. The titanium nitride layer includes a portion having an oxygen content of 1 at % or more.
2. The conjugate according to claim 1, wherein The amount of nitrogen in the portion of the titanium nitride layer is 20 at % or more.
3. The conjugate according to claim 1 or claim 2, wherein: A 20 nm×20 nm measurement area in the titanium nitride layer was subjected to regional analysis by TEM-EDX, and when the total amount of constituent elements other than carbon was set to 100 at %, The average value of the oxygen content in any five of the measurement areas is 1 at% or more, The average value of the nitrogen content in the five measurement areas is 20 at % or more.
4. The conjugate according to claim 3, wherein: The average value of the oxygen amount is within a range of 1 at % to 10 at %, The average value of the nitrogen amount is within a range of 50 at % to 65 at %.
5. The conjugate according to claim 4, wherein In any of the five measurement regions, the nitrogen amount is within a range of 50 at % to 65 at %, and the oxygen amount is within a range of 1 at % to 10 at %.
6. The conjugate according to claim 1 or claim 2, wherein: The bonding layer contains: Ti, At least one selected from the group consisting of Cu and Ag, and At least one selected from the group consisting of Sn, In, and C.
7. The conjugate according to claim 4, wherein: The bonding layer contains: Ti, At least one selected from the group consisting of Cu and Ag, and At least one selected from the group consisting of Sn, In, and C.
8. The conjugate according to claim 5, wherein: The bonding layer contains: Ti, At least one selected from the group consisting of Cu and Ag, and At least one selected from the group consisting of Sn, In, and C.
9. The conjugate according to claim 1 or claim 2, wherein: The bonding layer comprises: The titanium nitride layer, and a brazing material layer between the titanium nitride layer and the metal component, The brazing material layer includes a Ti-rich region containing more than 30 at % Ti, The amount of nitrogen in the Ti-rich region is in the range of 1 at % to 15 at %.
10. The conjugate according to claim 6, wherein The bonding layer comprises: The titanium nitride layer, and a brazing material layer between the titanium nitride layer and the metal component, The brazing material layer includes a Ti-rich region containing more than 30 at % Ti, The amount of nitrogen in the Ti-rich region is in the range of 1 at % to 15 at %. The joint body according to claim 10, wherein: When a measurement region of 20 nm×20 nm in the brazing material layer is analyzed by TEM-EDX, the measurement region includes the Ti-rich region.
12. The conjugate according to claim 10, wherein When observing the bonding layer in an arbitrary cross section, the area ratio of the Ti-rich region in the bonding layer is within a range of 5% to 30%.
13. The conjugate according to claim 1 or claim 2, wherein: The thickness of the titanium nitride layer is within a range of 0.1 μm to 2 μm.
14. The conjugate according to claim 5, wherein The thickness of the titanium nitride layer is within a range of 0.1 μm to 2 μm.
15. The conjugate according to claim 12, wherein The thickness of the titanium nitride layer is within a range of 0.1 μm to 2 μm.
16. The conjugate according to claim 5, wherein The metal members are bonded to both surfaces of the nitride-based ceramic member via the bonding layers.
17. The conjugate according to claim 10, wherein The metal members are bonded to both surfaces of the nitride-based ceramic member via the bonding layers.
18. A ceramic circuit substrate comprising the bonded body according to claim 5, The nitride-based ceramic component has a substrate shape, The metal member has a circuit shape.
19. A ceramic circuit substrate comprising the bonded body according to claim 10, The nitride-based ceramic component has a substrate shape, The metal member has a circuit shape.
20. A joined body comprising a nitride-based ceramic member and a metal member joined to the nitride-based ceramic member via a joining layer, The bonding layer comprises a Ti-rich region, When the sum of the Ti content, Sn content, Cu content, nitrogen content and oxygen content is set to 100at%, the Ti content of the Ti-rich region is 30at% or more and 50at% or less, the Sn content is 20at% or more and 40at% or less, the Cu content is 0at% or more and 20at% or less, the nitrogen content is 1at% or more and 15at% or less, and the oxygen content is 0at% or more and 3at% or less, The area ratio of the Ti-rich region is in the range of 5% to 30%.
Citation Information
Patent Citations
Ceramic-copper assembly and manufacturing method of the same
JP2013211546A
Bonded substrate, and method for manufacturing bonded substrate
WO2021015122A1
Bonded object production method and production method for ceramic circuit substrate using same
WO2022244769A1